2011
DOI: 10.1016/j.eswa.2011.01.121
|View full text |Cite
|
Sign up to set email alerts
|

A randomized model ensemble approach for reconstructing signals from faulty sensors

Abstract: On-line sensor monitoring aims at detecting anomalies in sensors and reconstructing their correct signals during operation. The techniques used for signal reconstruction are commonly based on auto-associative regression models. In full scale implementations however, the number of sensors to be monitored is often too large to be handled effectively by a single reconstruction model. In this paper we propose to tackle the problem by resorting to a pool (ensemble) of reconstruction models, each one handling an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…, measured in the plant, a set of K groups of mn  signals are generated by randomly sampling the signals from the n available [12][13][14]. The procedure is simple, allows a direct and fast group generation suitable for large scale applications, guarantees high signal diversity between the groups (and thus high diversity between the models outcomes, beneficial to ensemble reconstruction) and attains high signal redundancy, upon a reasonable choice of the ensemble parameters m and K [14].…”
Section: Methods Of Aggregation Of the Outcomes Of The Models In The mentioning
confidence: 99%
See 2 more Smart Citations
“…, measured in the plant, a set of K groups of mn  signals are generated by randomly sampling the signals from the n available [12][13][14]. The procedure is simple, allows a direct and fast group generation suitable for large scale applications, guarantees high signal diversity between the groups (and thus high diversity between the models outcomes, beneficial to ensemble reconstruction) and attains high signal redundancy, upon a reasonable choice of the ensemble parameters m and K [14].…”
Section: Methods Of Aggregation Of the Outcomes Of The Models In The mentioning
confidence: 99%
“…To do this, the data set X of N signal patterns available is partitioned into a training set X [12,14,20,21]; for the generic pattern 1, 2,..., ,( ) ( ) 1, 2,..., …”
Section: Methods Of Aggregation Of the Outcomes Of The Models In The mentioning
confidence: 99%
See 1 more Smart Citation
“…with overlapping, i.e., the same signal can belong to more than one group [12], [22]- [25], and without overlapping [26]- [28]. In practical applications, the latter strategy tends to be preferred because it allows for a smaller number of models to be developed, at a lower computational effort [28].…”
Section: Different Empirical Models Have Been Developed For Signal Rementioning
confidence: 99%
“…The 46-dimensional patterns (5798) have been divided into a set X M of 2798 patterns used to perform the hybrid signal grouping (Section 3), and a validation set X V of 3000 patterns used to validate the condition monitoring and fault detection scheme (Section 4). In [29], it has been shown that this hybrid method leads to reconstructions that are more tolerant to the fault propagation problem (that has been mentioned in the Introduction) than proceeding with the reconstruction based on the single group of all signals [19], [27], or on groups of signals defined by a filter CA approach only [19], [25], or by a wrapper GA-based approach only [28].…”
Section: The Case Studymentioning
confidence: 99%